2019
DOI: 10.1007/s40263-019-00626-2
|View full text |Cite|
|
Sign up to set email alerts
|

A Multi-Center, Open-Label, Pharmacokinetic Drug Interaction Study of Erenumab and a Combined Oral Contraceptive in Healthy Females

Abstract: Background Erenumab is a human anti-calcitonin gene-related peptide monoclonal antibody developed for migraine prevention. Migraine predominately affects women of childbearing age; thus, it is important to determine potential drug–drug interactions between a common oral contraceptive and drugs used to treat migraine. Objectives We sought to evaluate potential drug–drug interactions between erenumab and a common oral contraceptive. Methods Hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…From the pharmacokinetics perspective, as mAbs are eliminated via catabolic pathways, they may not compete directly with other small molecule drugs that are mainly eliminated via hepatic, renal, or biliary processes [32]. A study conducted in 2017 found that subcutaneous erenumab did not in uence the effect of estrogen/progestin combination oral contraceptives among healthy females [33]. A placebocontrolled trial investigating co-administration of erenumab 140 mg and sumatriptan 12 mg have found no additional effect on averages of mean arterial pressure or on the pharmacokinetics of sumatriptan [34].…”
Section: Discussionmentioning
confidence: 99%
“…From the pharmacokinetics perspective, as mAbs are eliminated via catabolic pathways, they may not compete directly with other small molecule drugs that are mainly eliminated via hepatic, renal, or biliary processes [32]. A study conducted in 2017 found that subcutaneous erenumab did not in uence the effect of estrogen/progestin combination oral contraceptives among healthy females [33]. A placebocontrolled trial investigating co-administration of erenumab 140 mg and sumatriptan 12 mg have found no additional effect on averages of mean arterial pressure or on the pharmacokinetics of sumatriptan [34].…”
Section: Discussionmentioning
confidence: 99%
“…Both these hormones are well-known active ingredients of several approved OCs. 7 During period 2, subjects were administered lemborexant 10 mg for 10 days starting on day 5 in the evening following the last OC PK sample. During period 3, lemborexant 10 mg was administered in the evening on days 15-18.…”
Section: Methodsmentioning
confidence: 99%
“…From Phase I studies [ 5 , 7 , 8 , 9 ], assessing the safety, tolerability, pharmacokinetics (PK), and pharmacodynamics (PD) of erenumab, it was shown that erenumab is a safe and well tolerable drug with linear PK for doses above from 70 mg, typical IgG2 mAb behavior, and a highly potent CGRP receptor inhibitor profile. At 70 mg, the estimated elimination half-life of erenumab is 21 days, supporting monthly subcutaneous dosing and thus improving patient compliance [ 5 , 8 , 10 ].…”
Section: Erenumabmentioning
confidence: 99%